Pendampingan Kegiatan Active Learning Berbasis Digital di SD N 2 Mranti Purworejo - Arum Ratnaningsih; Nurhidayati Nurhidayati; Ike Yunia Pasha (Surya Abdimas, 2018)
The purpose of community service activities is to facilitate teachers in mastering digital-based Active Learning learning. The method in community service activities uses the mentoring method. Based on the results achieved in the Active Learning assistance activities consisted of three things with the following explanation. First, increasing participants' insights on innovation in learning. This can be seen in the way learning has been done by trainees using the Active Learning approach, so that the realization of active, fun, and innovative learning is realized. Second, foster curiosity about technological innovation. The realization of the attitude of participants who always try various digital applications that can support the learning process. Third, provide direct learning experiences to participants. The learning experience was directly felt by the participants with the practical activities of the Active Learning approach that collaborates with digital applications. The purpose of learning activities using the Active Learning approach makes it easy for students to understand learning material so that learning becomes fun. Participation of partners in the implementation of community service programs includes providing a place in the form of Mranti 2 Elementary School building, providing facilities such as mic, sound, seating, LCD, computer, and food banquets, and participants who are enthusiastic in participating in community service activities.